2016
DOI: 10.1590/2317-1782/20162015270
|View full text |Cite
|
Sign up to set email alerts
|

Alterações Fonoaudiológicas no Transtorno de Déficit de Atenção e Hiperatividade: revisão sistemática de literatura

Abstract: RESUMO Objetivo revisar sistematicamente as produções científicas acerca das relações entre o Transtorno de Déficit de Atenção e Hiperatividade e a Fonoaudiologia e analisar, metodologicamente, os estudos observacionais sobre a temática. Estratégia de pesquisa trata-se de revisão sistemática de literatura, realizada nas bases de dados Medical Literature Analysis and Retrieval System on-line (MEDLINE, EUA), Literatura Latino-Americana e do Caribe em Ciências da Saúde (LILACS, Brasil) e Indice Bibliográfico Es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Grey literature publications were not covered in our search. Secondly, our inclusion criteria and threshold for quality assessment were quite strict, thus excluding some of the pertinent systematic reviews on topics including genetics [242][243][244][245][246][247][248][249], neurobiology [250,251], prevalence including young adults [252][253][254], comorbidities like dyslexia [255,256], speech disorder [257], borderline personality disorder [258] and nonpharmacological interventions in adults [259].…”
Section: Discussionmentioning
confidence: 99%
“…Grey literature publications were not covered in our search. Secondly, our inclusion criteria and threshold for quality assessment were quite strict, thus excluding some of the pertinent systematic reviews on topics including genetics [242][243][244][245][246][247][248][249], neurobiology [250,251], prevalence including young adults [252][253][254], comorbidities like dyslexia [255,256], speech disorder [257], borderline personality disorder [258] and nonpharmacological interventions in adults [259].…”
Section: Discussionmentioning
confidence: 99%
“…On this topic, there is no doubt that in the field of studies on the developmental trajectory of individuals with ADHD, performance in academic and cognitive skills underlying the reading and writing learning process has been systematically investigated, both in the national and international scientific scenario, as the review study showed (3) . On the other hand, there is little research on the performance of spoken language of individuals with ADHD, although difficulties both at the receptive and expressive level have been described in this clinical group (4) .…”
Section: Introductionmentioning
confidence: 99%
“…Lack of atention has a strong impact in memory skills and in the process of spelling and reading comprehension, which in turn, limits all learning process via writen input [1,22]. The diagnostic of speciic language impairment (SLI); there is an asynchrony on the development of linguistic subsystems in such a way that the deviant deicits will have consequences for the development of writen language [36].…”
Section: Introductionmentioning
confidence: 99%